Creating Language Environment at Al-Mashduqiah Islamic Education Center Patokan Kraksaan Probolinggo - Mamluatun Ni'mah; Edi Kurniawan Farid; Syamsul Ma'arif (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This research aims to know the programs for creating the language environment at Al-Mashduqiah Islamic Education Center Patokan Kraksaan Probolinggo, and describe the supporting and the obstacle factors in creating the language environment at Al-Mashduqiah Islamic Education Center Patokan Kraksaan Probolinggo. Design/methodology/approach - The researcher uses a qualitative research approach with a case study research design. The techniques that used for collecting data are observation, interview and documentation. Findings - The result of this research, the programs for creating the language environment at Al-Mashduqiah Islamic Education Center Patokan Kraksaan Probolinggo there are delivering of vocabularies, repeating of vocabularies, language clubs, language court, public speaking, conversation, language month, language competition, and repairing. The Supporting and the obstacle factors in creating the language environment at Al-Mashduqiah Islamic Education Center Patokan Kraksaan Probolinggo consist of internal factors and external factors. Originality/value – Depend on the results of this research that to creat the language environment needs some efforts such as doing the language programs, practising, implementing an effective language teaching method, and implementing the language games to reduce boredom and to motivate students in learning a foreign language. Paper type – Research Paper